EFFECT OF NEGATIVE REDOX POTENTIAL OF DRY SEDIMENT ON THE INFECTIVITY OF Vibrio parahaemolyticus, GROWTH AND HEALTH STATUS OF PACIFIC WHITELEG SHRIMP - Putri, Shofii Amaliah; Sukenda, Sukenda; Yuhana, Munti; Nirmala, Kukuh (Indonesian Aquaculture Journal, 2025)
Sediment serves as a site for the accumulation of aquaculture waste. Oxidation-Reduction Potential (ORP) is an index indicating anaerobic conditions. A combination of host, pathogen, and suboptimal environmental quality can lead to disease outbreaks. One such disease is Acute Hepatopancreatic Necrosis Disease (AHPND), caused by Vibrio parahaemolyticus. This study was aimed to analyse the impact of sediment drying on infectivity of V. parahaemolyticus growth and health status of Pacific whiteleg shrimp. The sediment ORP used at the initial study was -37 mV. The sediment was dried for 120 hours at a temperature of 40.75 ± 2.73 °C. A total of 15 shrimp/aquarium with an average body weight of 2.35±0.22 g/individual were reared in aquarium sized 20x25x30 cm3 containing dried and undried sediment for 120 hours, then contaminated with 105 CFU/mL V. parahaemolyticus through immersion from the start of rearing until 20 days later. The results showed that sediment drying was able to reduce bacterial abundance and increase ORP sediment. The longer duration of cultivation, the more the sediment ORP decreased. Sediment ORP decreased with increasing shrimp farming duration. The highest bacterial abundance in the sediment on thrid phase of study was observed in the positive control treatment on D+10 ((2.02±0.39)x104 CFU/g), then it decreased until the end. Meanwhile, bacterial abundance in water and hepatopancreas decreased until the end of the study. Survival rates, immune responses, and growth parameters of shrimp with sediment drying were higher than the positive control (p<0.05) but not significantly different from the negative control. The histopathology of shrimp hepatopancreas profile in the sediment drying treatment was better compared to the positive control.